Pengaruh Kualitas Informasi, Nilai Yang Dirasakan Pelanggan, dan Kualitas Pengalaman Terhadap Kepuasan Pelanggan Pada Shopeefood - Marchellino Ronaldo Sae; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to determine how the influence of information quality, customer perceived value, and experience quality on customer satisfaction at Shopeefood. The population in this study were students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa with a total sample of 93 respondents. The data sample selection in this study was carried out by purposive sampling, namely with students who made transactions more than twice as well as the 2019 and 2020 batches. The data collection method was using a questionnaire distributed online via Google Form. To test the quality of the data in this study using Validation Test and Reliability Test. The data analysis technique in this study used the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, T Test, and Coefficient of Determination. The results of the data are processed using the help of IBM SPSS. The results showed that the quality of information had a significant value of 0.018, the customer perceived value had a significant value of 0.043, and the quality of experience had a significant value of 0.000, which means that information quality, customer perceived value, and experience quality have a significant influence on customer satisfaction at Shopeefood.